GAMBARAN SEKTOR KETENAGAKERJAAN DAN KEMISKINAN DI PROVINSI BENGKULU - Muhammad Basorudin; Rizka Heryanti; Nadia Humairo; Anggoro Widyapuji Putro; Alfada Maghfiri Firdani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2019)
Employment is the best way to get out of poverty. One effort to reduce poverty levels is utilization of the workforce at productive age. Uniquely, this condition doesn’t work for Bengkulu Province. Poverty is still being serious problem and unfortunately labor force participation rate is high. This case made big question, what cause of disobedience for Bengkulu Province, so it’s interesting to do analysis. The analysis used primary data from Susenas (National Sosioeconomic Survey) and used descriptive analysis method, which independent variable are locational (rural/urban), sex, last education, employment status, and employment opportunities. The result showed that employment opportunities indicates the existence of influence to poverty.